2012
DOI: 10.1126/science.1214463
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Brain Structure Implicated in Stimulant Drug Addiction

Abstract: Addiction to drugs is a major contemporary public health issue, characterized by maladaptive behavior to obtain and consume an increasing amount of drugs at the expense of the individual's health and social and personal life. We discovered abnormalities in fronto-striatal brain systems implicated in self-control in both stimulant-dependent individuals and their biological siblings who have no history of chronic drug abuse; these findings support the idea of an underlying neurocognitive endophenotype for stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

41
418
6
4

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 502 publications
(469 citation statements)
references
References 41 publications
41
418
6
4
Order By: Relevance
“…In addition, our novel surface area and shape findings provide more nuanced insight into the relationship between striatal morphology and craving. The relationship between craving and left lateralized striatal volume and surface area is consistent with previous findings linking stimulant abuse with greater left striatal volume (Das et al, 2011;Churchwell et al, 2012, Ersche et al, 2012. The connection between the left striatum and substance abuse may be tied to the more dominant role of the left hemisphere in reward and approach behavior (Davidson and Irwin, 1999).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In addition, our novel surface area and shape findings provide more nuanced insight into the relationship between striatal morphology and craving. The relationship between craving and left lateralized striatal volume and surface area is consistent with previous findings linking stimulant abuse with greater left striatal volume (Das et al, 2011;Churchwell et al, 2012, Ersche et al, 2012. The connection between the left striatum and substance abuse may be tied to the more dominant role of the left hemisphere in reward and approach behavior (Davidson and Irwin, 1999).…”
Section: Discussionsupporting
confidence: 87%
“…For example, enhanced striatal surface area has been associated with obsessive-compulsive disorder (OCD; Shaw et al, 2014), suggesting that larger striatal surface area may be a feature of compulsive disorders including OCD and addiction. Finally, our research focused only on the relationship between striatal morphology and cigarette craving as previous research has shown a clear link between stimulant abuse and enhanced striatal volume when substance abusers and healthy controls were compared (Das et al, 2011;Churchwell et al, 2012, Ersche et al, 2012. It is unclear whether variability in striatal morphology, in non-abusing populations also may explain individual differences in craving severity for other, more natural, reinforcers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, METH users have enlarged striatal structures, such as the putamen (Chang et al, 2005a;Ersche et al, 2012), globus pallidus (Chang et al, 2005a), and nucleus accumbens. (Jernigan et al, 2005) Chang et al found that METH users with enlarged striatum had relatively normal cognitive performance, suggesting a compensatory response to maintain cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, compared to cocaine-dependent participants, METH-dependent participants had significantly greater BIS nonplanning and total scores (Winhusen et al, 2013). While most studies cannot conclude whether METH use caused abnormal brain structures or impulsive behavior, one study suggested that gray matter dorsal striatum changes may predispose individuals for an increased risk for developing stimulant dependence (Ersche et al, 2012). Ersche et al evaluated stimulant dependent users, their non-drug using siblings, and unrelated CON and found gray matter changes in the dorsal striatum and higher impulsivity in both the stimulant users and their siblings compared to the CON.…”
Section: Introductionmentioning
confidence: 99%